2018
DOI: 10.21608/asejaiqjsae.2018.5504
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biosurfactant Producing Microorganisms to Remediate Heavy Metal Pollution in El-Gabal El-Asfar Area

Abstract: In the present study, the effects of biosurfactant producing cells of different bacterial species namely Pseudochrobactrum lubricantisa, Lysobacter novalis, and crude biosurfactant extracted from Aspergillus niger were investigated as a cheap source to alleviate the availability of Pb 2+ for plants grown in El-Gabal El-Asfar area, Egypt. This is owing to these areas are basically depend on the reused wastewater for irrigation. Biosurfactant producing microorganisms were isolated from three different farms aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…While the application of mixed biofertilizer cultures in growing season 2017/2018 increased about 75.2, 87.2 and 75.6% in available nitrogen and 49.1, 74.3 and 58.1% in available phosphorus over the control at 50, 75 and 100% of chemical fertilizers, respectively. Similar results were obtained by Yaseen et al (2018), who found that the most significant factor affected NPK availability in soil was biosurfactant producing bacteria. PGPR play an essential role in nutrient cycling in soils, they involved in processes such as oxidation, nitrification, ammonification, nitrogen fixation, and other processes which lead to decomposition of soil organic matter and releasing essential inorganic plant nutrients to the soil.…”
Section: Effect Of Mineral Fertilizer Levels and Biofertilizers On Available Minerals In The Rhizosphere Of Barley Plant During 2016-2017supporting
confidence: 88%
“…While the application of mixed biofertilizer cultures in growing season 2017/2018 increased about 75.2, 87.2 and 75.6% in available nitrogen and 49.1, 74.3 and 58.1% in available phosphorus over the control at 50, 75 and 100% of chemical fertilizers, respectively. Similar results were obtained by Yaseen et al (2018), who found that the most significant factor affected NPK availability in soil was biosurfactant producing bacteria. PGPR play an essential role in nutrient cycling in soils, they involved in processes such as oxidation, nitrification, ammonification, nitrogen fixation, and other processes which lead to decomposition of soil organic matter and releasing essential inorganic plant nutrients to the soil.…”
Section: Effect Of Mineral Fertilizer Levels and Biofertilizers On Available Minerals In The Rhizosphere Of Barley Plant During 2016-2017supporting
confidence: 88%
“…These results showed that SAP aids to increase the capacity of soil cationic exchange and better absorption of water and nutrition materials; that is the result of not washing the water and fertilizers. Yaseen et al (2018) also reported that PGPR was the most significant factor affected NPK availability in soil.…”
Section: Evaluation Of Nutrient Availability (Npk) In Soilmentioning
confidence: 94%
“…In addition, Lysobacter has a significant positive correlation with most heavy metals/metalloids ( Supplementary Figure 3 ). Lysobacter belongs to the phylum Proteobacteria, which have been reported to be tolerant to Hg, As, Cr, Pb, Co, Cu, and Zn ( Brito et al, 2013 ; Puopolo et al, 2016 ; Yaseen et al, 2018 ; Wang et al, 2020b ). Yaseen et al (2018) have confirmed that Lysobacter novalis can reduce A-Pb in soil by producing biosurfactants.…”
Section: Discussionmentioning
confidence: 99%
“…Lysobacter belongs to the phylum Proteobacteria, which have been reported to be tolerant to Hg, As, Cr, Pb, Co, Cu, and Zn ( Brito et al, 2013 ; Puopolo et al, 2016 ; Yaseen et al, 2018 ; Wang et al, 2020b ). Yaseen et al (2018) have confirmed that Lysobacter novalis can reduce A-Pb in soil by producing biosurfactants. It is worth noting that Gemmatimonas of the phylum Gemmatimonadetes, and Flavisolibacter and Chitinophaga of the phylum Bacteroides also exhibit heavy metal/metalloid resistance in this work.…”
Section: Discussionmentioning
confidence: 99%